METHODOLOGY AND MODEL FOR THE STUDY OF RELATIVE ACCURACY DEVIATION IN LASER CUTTING OF C 235 STEEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents an analysis using the design methodology based on the response of investigated quantities in the optimization of laser cutting parameters in terms of dimensional accuracy for C235 steel samples. The input factors, such as cutting speed, power, and carbon dioxide pressure, on the quality cut, expressed by the relative deviation from accuracy, are examined. The paper proposes an algorithm and a regression model to optimize the deviation from the dimensions between a model and a cut contour, by minimizing the error of this deviation. Based on the conducted experiment and research results, a generalized methodology was created. It can be used after a planned experiment to determine the accuracy of any contours of a test material of a specific thickness.